Evaluation of the chemical composition and surface acidity of mesoporous acidic catalysts in the production of 5-hydroxymethylfurfural and furfural from monosaccharides - Vieira, José Lucas (2024)
This thesis investigates the synthesis, composition, and surface acidity of various mesoporous acidic catalysts and their impacts on the catalytic dehydration of monosaccharides into the platform molecules 5-hydroxymethylfurfural (HMF) and furfural. Niobium phosphates with different P/Nb molar ratios were prepared, affecting their Lewis/Brønsted acid site (L/B) ratio and catalytic activity. Catalysts with high P/Nb ratios exhibited low L/B ratios, whereas catalysts with low P/Nb ratios, high L/B ratios. Additionally, a linear correlation between the L/B ratio and reaction rates for HMF and furfural production from glucose and xylose, respectively, was demonstrated. Based on that, we synthesize a controlled mesoporous bifunctional carbon catalyst to more easily produce a catalyst with L/B ratios for platform molecules production. First, we prepared sulfonated carbons with only Brønsted acidity for the dehydration of fructose and xylose into HMF and furfural, respectively. They had different concentrations of stronger (sulfonic acid groups) and weaker acid sites (carboxylic acid, alcohol, phenol groups). The ratio between stronger and weaker acid sites (NS/NW) was found to significantly influence catalytic performance, with optimal yields and turnover numbers observed at NS/NW ratios of 2 – 4, suggesting a synergistic role of both types of acid sites in the catalytic mechanism. Finally, two promising sulfonated carbons from the previous study were selected and underwent partial ion-exchange with metallic cations with Lewis acidity (Al3+, Sc3+, Fe3+, Cu2+, Sn4+, Yb3+) to produce ion-exchanged bifunctional carbons with different L/B ratios for dehydrating glucose and xylose into HMF and furfural, respectively. Even though no characterization regarding surface acidity has been performed yet, the strength of the Lewis acid sites likely plays a crucial role in the monosaccharide conversion, with stronger sites (Al3+, Cu2+, and Yb3+) leading to isomers; intermediate strength sites (Sc3+) leading to both isomers and platform molecules, and weaker sites (Sn4+) leading to platform molecules. The catalyst with 20 % of Brønsted acid sites exchanged with Sn4+ (20%-Sn(IV)-Amb-45) showed promising results, achieving 41 % HMF selectivity at 57 % glucose conversion and 47 % furfural selectivity at 65 % xylose conversion, whereas 100%-Al(III)-Amb-45, 100%-Cu(II)-Amb-45, and 100%-Yb(III)-Amb-45 were promising for isomerization reactions.